ANALISIS KESIAPAN PUSKESMAS SEBAGAI PROVIDER BPJS KESEHATAN (STUDI DI PUSKESMAS KEDUNGMUNDU DAN PUSKESMAS TLOGOSARI KULON) - Prativi, Adhinda Nur; Suryawati, Chriswardani; Arso, Septo Pawelas (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Indonesian government is developing a national helath insurance program held by national health security board (BPJS) to support the implementation of the Universal Health Coverage. Implementation of the program national health security was applied at all levels of health care facilities, ranging from primary to tertiary. In a national health insurance program primary health care has an important role by becoming the gate-keeper so hopefully most of health services finished at primary level. However, not all primary health care have an adequate amount of resources to serve patients. On the other hand the number of patients BPJS participants also continued to increase every month.Research conducted by qualitative study aimed to describe the readiness of Puskesmas Kedungmundu and PuskesmasTlogosari Kulon in the implementation of health insurance program with input and process variable. The subjects were the head of the primary health care, service manager, financial managers, and doctor. Informants triangulation is the head of primary health care management of national health security board and patient. The results reveal that the variables of human resources, financial management processes, infrastructure, regulations BPJS, BPJS patient care process including time and market aspects of the health center is ready to support the implementation of the program JKN at primary level, although there are still some things that need to be repaired or reviewed . Human resources in general still requires additional staff, such as administrative staff, medical personnel and paramedics, socialization aspect is sufficient but need added financial management training; funding comes from capitation, BOK and budget of regional goverment , capitation fund management procedures are in accordance with predetermined rules, but should soon be published rules regarding the management is more detailed; infrastructure is complete but requires repair or rejuvenation; required additional regulations on financial management; The process of patient care; necessary socialization of policies or regulations of national health security board membership to the patient in order to avoid miscommunication, the number of participants continues to grow, the quality of service must be maintained, patient service time is in conformity with the standards.